2021
DOI: 10.7759/cureus.18182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Infection on Quality of Sleep

Abstract: Introduction: Some studies have highlighted the effect of COVID-19 infection on the quality of sleep; however, the data is limited. In this study, we investigated the prevalence of insomnia in patients who recently recovered from the COVID-19 infection to evaluate the prevalence and extent of its impact.Methods: This longitudinal study was conducted from January 2021 to March 2021. A total of 500 patients admitted to the intensive care unit or isolation unit of COVID-19 were included in the study at the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…Due to different study objectives, the full-text revision resulted in elimination of 138 studies, and 8 were enlisted for final data extraction (Figure 1) and (Table 1). Choudhry et al [17] patients with recovered COVID-19 have a statistically significant prevalence of sleeplessness after 30 days of follow-up. Additionally, 215 recovered patients (84%) in Al-Ameri et al [18] research's control group outnumbered 384 patients (78%) had sleep problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to different study objectives, the full-text revision resulted in elimination of 138 studies, and 8 were enlisted for final data extraction (Figure 1) and (Table 1). Choudhry et al [17] patients with recovered COVID-19 have a statistically significant prevalence of sleeplessness after 30 days of follow-up. Additionally, 215 recovered patients (84%) in Al-Ameri et al [18] research's control group outnumbered 384 patients (78%) had sleep problems.…”
Section: Resultsmentioning
confidence: 99%
“…The research's findings showed to individuals reported a considerably higher prevalence of sleeplessness when they had long-term COVID with a usually poorer standard of living (QOL). In a collection of post-COVID-19 cases 22% of patients who were assessed by ISI after being discharged from the University of Virginia ICU reported having insomnia for the first time during a six-week checkup [17,25]. It is unusual that patients who recovered from COVID-19 to have considerably higher PSQI scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation inquired about the pre-COVID-19 sleep quality of the patients and the same aspect was assessed 30 days after discharge. The results revealed that the PSQI score was significantly higher in the post-COVID-19 group compared to the pre-COVID-19 group with 45.1% of the participants reporting a PSQI score of >5, signifying a poor quality of sleep at the 30-day post-recovery follow-up, whereas only 12.1% of the participants had reported poor quality of sleep before contracting the infection (50). Post-COVID-19 sleep disturbances were reported by 500 post-COVID-19 patients in the recovery period, and were associated with an impact on the physical and mental aspects of the quality of life of these patients (51).…”
Section: Insomnia and Covid-19 Infectionmentioning
confidence: 91%
“…Published studies so far suggest that the prevalence of sleep disorders is significantly higher in the post-COVID-19 group compared to the pre-COVID-19 group among those patients admitted to the intensive care unit or isolation unit. [ 14 ] While sleep disorders in patients can be attributed to the course of the acute phase of infection and side effects of medications, they are also present in the course of long-term COVID-19 [ 15 ]. The meta-analyses on the prevalence data showed that common residual symptoms among COVID-19 survivors at one-year post infection included fatigue/weakness (28%), dyspnoea (18%), arthromyalgia (26%), depression (23%), anxiety (22%), memory loss (19%), concentration difficulties (18%), and insomnia (12%) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%